(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The modern technological world is based on the interaction of professionals from different countries and cultures. To become full-fledged members of the global scientific, business and socio-cultural community, students of technical universities must not only acquire foreign languages of intercultural communication but also get an idea of the world culture in all its diversity. This study examines a technical university student's cultural and English language proficiency through a digital culture-related course for self-learning and flipped classroom activities. Culture is a complex and multi-faceted concept that may be challenging for students to attain fully. Thus, a variety of representative cultural elements was selected for the course, which is comprised of three modules supporting the formation of competencies in such cultural spheres as social interaction, spiritual culture, and science and technology. The course was digitalized using audiovisual translation and implemented at Kharkiv National Automobile and Highway University in the 2022–2024 academic years. To study the effectiveness of the course, an experiment was conducted with the aim, firstly, to identify how the level of educational autonomy changed in the two groups of students: those who studied the course using digital technologies (an experimental group) and those taught in a traditional format (a control group); and, secondly, to compare the level of assimilation of culture-related English language vocabulary in both groups. In this research, we applied both quantitative and qualitative methods to assess the results of the experimental work that proved the positive impact of the proposed approach on the student’s linguistic and cultural competencies. The course contributes to raising intellectually, culturally, and multi-culturally developed citizens with a deep awareness of cultural values. It can be used as a template for creating innovative digital language learning resources.